A Scaffolding Approach Using Interviews and Narrative Inquiry - Sharon Heilmann (Networks: An Online Journal for Teacher Research, 2018)
This article examines how educational scaffolding was used in a graduate research methods course to encourage student mastery of two qualitative research concepts, interviews and narrative inquiry. Findings suggest that scaffolding resulted in students’ mastery of both concepts as well as students’ increased attention to quality of interview questions and outcomes. Further implications suggest scaffolding would be useful in combining other qualitative topics such as integrating content analysis skills with research designs such as phenomenology, grounded theory, and case studies.
Keywords: Narrative Inquiry; Interviews; Qualitataive Methods; Scaffolding; Teaching